Foreign and domestic investment in global bond markets - Donghyun Park; Kiyoshi Taniguchi; Shu Tian (Asian Development Bank (ADB), 2018)
Gauging foreign (domestic) biases as the deviation of foreign (domestic) investors' actual portfolio allocation of a bond market from the same bond market's weight in global bond market, we investigate the determinants of foreign and domestic investment biases in 41 global bond markets. We find that foreign investors significantly overweigh markets that offer better risk-return profiles. In addition, greater market openness and sound macroeconomic outlook attract foreign investment. Such return driven behavior of foreign investors is especially pronounced in emerging bond markets. Meanwhile, home bias is higher in smaller bond markets. Our evidence sheds some light on the role of regional financial integration on broadening investor base and improving investor profile in emerging markets.
Keywords: F30; G11; G15; G20; 330; bond market; financial integration; home bias; portfolio decisions